Antibacterial Activity of Fractions from Extract Ethanolic of Hylocereus Polyrhizus Peel Against E. Coli and S. aureus - Tsania Khusnul Khotimah; Annisa Krisridwany; Salmah Orbayinah; Sabtanti Harimurti (Universitas Muhammadiyah Yogyakarta, 2021)
Peel of red dragon fruit (Hylocereus polyrhizus) is one of the plants used as an antibacterial agent as it contains saponin triterpenoid compounds, flavonoid compounds, and alkaloid compounds which can have antibacterial activity. This research aims to determine the antibacterial effect of n-hexane, ethyl acetate, and ethanol fraction of red dragon fruit’s peel against Escherichia coli and Staphylococcus aureus by the concentration of 10mg/ml, 20mg/ml, 40mg/ml, 80mg/ml dan 160mg/ml. This research was conducted by using laboratory experiments. The simplicia was macerated with 96% ethanol and fractionated by n-hexane and ethyl acetate. The phytochemical screening of the fraction was n-hexane fraction containing saponin and alkaloid, while the ethyl acetate fraction contained saponin and flavonoid. Kanamycin was used as a positive control, while DMSO was used as a negative control. According to this research, the MIC value of ethanol fraction, n-hexane fraction, and ethyl acetate fraction were 80mg/ml, 20mg/ml, and 80mg/ml, respectively, for E. coli and all fractions were 10mg/ml for S. aureus. Based on the average diameter of the inhibition zone, the largest diameter zone in E. coli was ethyl acetate fraction with 160mg/ml concentration that was 10,33mm. Meanwhile, in S. aureus n-hexane fraction, it was 160mg/ml, which was 11,20mm. This result showed that the n-hexane fraction has good gram-positive activity while the ethyl acetate fraction has good activity on gram-negative.